REVERSE phenotyping—Can the phenotype following constitutive Tph2 gene inactivation in mice be transferred to children and adolescents with and without adhd?. Issue 5 (1st February 2021) - Akhrif, Atae; Roy, Arunima; Peters, Katharina; Lesch, Klaus‐Peter; Romanos, Marcel; Schmitt‐Böhrer, Angelika; Neufang, Susanne
Abstract: Introduction: Experimental models of neuropsychiatric disorders, for example, ADHD, are used to mimic specific phenotypic traits of a complex human disorder. However, it remains unresolved to what extent the animal phenotype reflects the specific human trait. The null mutant mouse of the serotonin‐synthesizing tryptophan hydroxylase‐2 ( Tph2 ‐/‐ ) gene has been proposed as experimental model for ADHD with high face validity for impulsive, aggressive, and anxious behaviors. To validate this ADHD‐like model, we examined the Tph2 ‐/‐ phenotype in humans when considering allelic variation of TPH2 function ("reverse phenotyping"). Methods: 58 participants (6 females, 8–18 years) were examined, of whom 32 were diagnosed with ADHD. All participants were phenotyped for impulsivity, aggression, and anxiety using questionnaires, behavioral tests, and MRI scanning while performing the 4‐choice serial reaction time task. Additionally, participants were genotyped for the TPH 2 G‐703T (rs4570625) polymorphism. To analyze the relation between TPH 2 G‐703T variants and the impulsive/aggressive/anxious phenotype, mediation analyses were performed using behavioral and MRI data as potential mediators. Results: We found that the relation between TPH 2 G‐703T and aggression as part of the reverse Tph2 ‐ / ‐ phenotype was mediated by structure and function of the right middle and inferior frontal gyrus. Conclusion: At the example of trait aggression, our results support the assumption that the Tph2 null mutant mouse reflects the TPH 2 G‐703T‐ dependent phenotype in humans. Additionally, we conclude that "reverse phenotyping" is a promising method to validate experimental models and human findings for refined analysis of disease mechanisms. Abstract : The Tph2 ‐/‐ mouse has been proposed as an experimental model for ADHD. Translation of an animal phenotype into humans to examine its face validity (reverse phenotyping). Phenotyping included impulsivity, aggression, and anxiety, reflecting comorbid conditions of ADHD. Use of the RDoC approach to address phenotype dimensions in an isolated manner.